Impact of domestic and foreign investors on ESG disclosure quality in Chinese listed firms: Divergence or convergence? - Wei Yin; Yang Su; Berna Kirkulak-Uludag; An Yan; Ruizhe Wang (PLoS ONE, 2025)
Using the data of Chinese listed firms, this study constructs a two-layer complex network of Qualified Foreign Institutional Investors (QFII) and Domestic Institutional Investors (DII) to examine their influence on the quality of corporate ESG disclosures. By analyzing the credibility, consistency, and completeness of the network, it finds that improving a firm’s position within the QFII-DII complex network significantly enhances ESG disclosure quality. Key drivers include the knowledge transfer effect, information exchange effect, and market supervision effect. Additionally, executive green awareness and strong internal governance amplify the positive impact of network position on ESG quality. The study also reveals variations in the influence of QFII and DII over time and across industries, with similar overall effects. However, companies with higher centrality in the DII network layer are more likely to engage in ESG greenwashing behavior.